AFM Probing of Amyloid-Beta 42 Dimers and Trimers - Maity, Sibaprasad; Lyubchenko, Yuri L. (Frontiers in Molecular Biosciences, 2020)
Elucidating the molecular mechanisms in the development of such a devastating neurodegenerative disorder as Alzheimer’s disease (AD) is currently one of the major challenges of molecular medicine. Evidence strongly suggests that the development of AD is due to the accumulation of amyloid β (Aβ) oligomers; therefore, understanding the molecular mechanisms defining the conversion of physiologically important monomers of Aβ proteins into neurotoxic oligomeric species is the key for the development of treatments and preventions of AD. However, these oligomers are unstable and unavailable for structural, physical, and chemical studies. We have recently developed a novel flexible nano array (FNA)-oligomer scaffold approach in which monomers tethered inside a flexible template can assemble spontaneously into oligomers with sizes defined by the number of tethered monomers. The FNA approach was tested on short decamer Aβ(14-23) peptides which were assembled into dimers and trimers. In this paper, we have extended our FNA technique for assembling full-length Aβ42 dimers. The FNA scaffold enabling the self-assembly of Aβ42 dimers from tethered monomeric species has been designed and the assembly of the dimers has been validated by AFM force spectroscopy experiments. Two major parameters of the force spectroscopy probing, the rupture forces and the rupture profiles, were obtained to prove the assembly of Aβ42 dimers. In addition, the FNA-Aβ42 dimers were used to probe Aβ42 trimers in the force spectroscopy experiments with the use of AFM tips functionalized with FNA-Aβ42 dimers and the surface with immobilized Aβ42 monomers. We found that the binding force for the Aβ42 trimer is higher than the dimer (75 ± 7 pN vs. 60 ± 3 pN) and the rupture pattern corresponds to a cooperative dissociation of the trimer. The rupture profiles for the dissociation of the Aβ42 dimers and trimers are proposed. Prospects for further extension of the FNA-based approach for probing of higher order oligomers of Aβ42 proteins are discussed.